Praktikalitas E-Learning Berbasis Web di SMK Dhuafa Padang Tahun Ajaran 2022-2023 - Riza Azizi; Astri Indah Juwita; Rahmatul Husna Arsyah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This research is motivated by the problem of limited learning media at SMK Dhuafa Padang. This happens because there is no media-based learning that is attractive and effective. Therefore, the author seeks to design and create learning media for e-learning based on the Web at SMK Dhuafa Padang. This study uses research and development (R&D) methods. The research model used is the Borg & Gall development model, with the design and development steps as follows: Research and Information Gathering Stage (literature study, field study, user analysis); Planning (strengths, weaknesses, opportunities, threats); Product Development (waterfal: analysis, design, code); Product Testing and Revision (instrument validation, media validation); Final Product Revision (field trials, practicality, effectiveness); Dissemination. The research subjects were 75 students and 10 teachers. The results of the validity test by the experts as a whole are an assessment of the validity of E-learning based Web in Padang Dhuafa Vocational School of 88.53%, so that the validity level can be interpreted as very valid for use. The results of the practicality test assessment as a whole practicality assessment of E-learning based Web in Padang Dhuafa Vocational School were 94.49%, so that the level of practicality can be interpreted as being very practical to use. The results of the overall effectiveness test assessment of the effectiveness assessment E-learning based Web in Dhuafa Padang Vocational School were 94.85%, so that the level of effectiveness can be interpreted as being used very effectively.